Puzzle for the secret seven - Blyton, Enid. (b, 2004)
The Seven see a house burn down, then they witness the theft of a valuable violin. They try to discover if the two incidents are connected.
Keywords: Secret Seven (Fictitious characters) -- Juvenile fiction; Secret Seven (Fictitious characters)